University company cooperation development in Ukraine - Shcherbata, T. (Видавництво Львівської політехніки, 2016)
The university company cooperation (UCC) plays great role in economic, innovative, technological and scientific development. For more than 25 years, many Ukrainian business and academic leaders have high interest in cooperation and mutual research between their companies and universities. Only a few universities had cooperation with enterprises, mostly in technical area. The aim of the article is to underline the key points of UCC and to present proposition of mutual cooperation development in Ukraine. The article presents the ecosystem model that includes main types of partnership relations (in R&D, mobility of students, commercialization of R&D, curriculum development and delivery, lifelong learning, entrepreneurship and governance), target audience (stakeholders) and strategic factors of cooperation creating (strategies, structures, activities and framework conditions). Cooperation development in Ukraine depends on ages of academics working in the university, ages of leaders working in business, the area of knowledge, the type of university, the location of representatives. The main barriers of cooperation between university and company and their influence on the Ukrainian environment are presented. The key barriers of cooperation development in Ukraine include: lack of financial resources, lack of contact people, corruption and bureaucracy. Also in Ukraine most academics are not engaged in cooperation with business. The win-win partnership benefits for students, academics, companies, government, society are shared in the article. They include economic development, better performance of the business, equipment modernization, high level of knowledge transfer, stability on the labor market, innovation activity, practical knowledge and skills of the graduates, achieving the mission of the HEI. One of the best practices of successful strategic university company cooperation development in Ukraine was TEMPUS project of NEFECIE (National Education Framework for Enhancing IT Students’ Innovation and Entrepreneurship). The results of the project were creating a Virtual Innovative Space, promotion of students entrepreneurship and innovation projects IT-Eureka! Ukraine, creating new educational courses and others. The propositions for future partnership relation that was increase in Ukraine are given and contained encouraging students and academics to take part in Erasmus, Horizon 2020 programs; developing activities to support students in innovation entrepreneurship; promotion a good practice and success in existing UCC; developing different tools for better partnership relations; inviting business delegates to the universities and create common courses; informing academics about possible cooperation; creating development programs, agencies for supporting cooperation; increasing collaboration with the HR department of companies to offer students greater opportunities for practices and others. Future strategic partnership will force economic growth, competitiveness and make challenges in Ukrainian society. Кооперація між підприємством та університетом відіграє важливу роль в економічному, інноваційному, технологічному та науковому розвитку країни. Подано модель екосистеми, що містить основні типи партнерських стосунків, контактні аудиторії, стратегічні фактори розвитку кооперації. Зазначено основні бар’єри розвитку взаємодії в Україні, а також вплив партнерства на навколишнє середовище. Наведено переваги партнерства типу “win-win” для студентів, викладачів, науковців, компаній, уряду та суспільства. Розроблено можливі варіанти розвитку кооперації між підприємством та університетом в Україні.
Розвиток кооперації “підприємство – університет” в Україні
Keywords: університет; компанія; кооперація; партнерські відносини; university; company; cooperation; partnership relations